2013
DOI: 10.1002/grl.50686
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel projections and uncertainties of irrigation water demand under climate change

Abstract: [1] Crop irrigation is responsible for 70% of humanity's water demand. Since the late 1990s, the expansion of irrigated areas has been tapering off, and this trend is expected to continue in the future. Future irrigation water demand (IWD) is, however, subject to large uncertainties due to anticipated climate change. Here, we use a set of seven global hydrological models (GHMs) to quantify the impact of projected global climate change on IWD on currently irrigated areas by the end of this century, and to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
269
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 337 publications
(295 citation statements)
references
References 34 publications
21
269
0
5
Order By: Relevance
“…In 2055, there was no expressive IWR, and the production will probably be little affected by variations in the rainfall regime. However, according to Wada et al (2013), future water demands for irrigation (IWR) are subject to great uncertainties owing to anticipation of climate and changes in precipitation variability.…”
Section: Future Irrigation Water Requirements (Iwrs)mentioning
confidence: 99%
“…In 2055, there was no expressive IWR, and the production will probably be little affected by variations in the rainfall regime. However, according to Wada et al (2013), future water demands for irrigation (IWR) are subject to great uncertainties owing to anticipation of climate and changes in precipitation variability.…”
Section: Future Irrigation Water Requirements (Iwrs)mentioning
confidence: 99%
“…Neglecting the reaction of crops to increased CO 2 may lead to an overestimation of future irrigation water demand Elliott et al 2014;Gerten et al 2014). In the multi-model study of Wada et al (2013), the only model that considered CO 2 effects on crop photosynthesis and transpiration shows a decreasing trend in future irrigation water demand (about 10 % by the end of this century) and increasing yields, while model runs without CO 2 effect indicated pronounced increases in future irrigation water demand ([20 % by the end of this century).…”
Section: Quantification Of the Role Of Active Vegetation Under Changimentioning
confidence: 99%
“…In rain-fed cropland or irrigation-free seasons, evapotranspiration has a complex dependence on meteorological conditions (Wang and Dickinson, 2012) because E act also depends on the soil moisture content (Eq. 3).…”
Section: Sensitivity Experiments With Hypothetical Bias In Humiditymentioning
confidence: 99%
“…Recently, studies on irrigation water published as ISI-MIP Fast Track results have reported future changes in its seasonality (Wada et al, 2013) and the possibility of reduced water availability in river basins due to increasing demand for irrigation water . In both papers, the authors reported that there are large differences in the future projections of hydrological elements among the GHMs.…”
Section: Caveats On Different Sensitivities Of Evapotranspiration To mentioning
confidence: 99%
See 1 more Smart Citation